2023
DOI: 10.1021/acs.analchem.3c01647
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemiluminescence of Porphyrin via Crystalline Networks of Metal–Organic Frameworks for Sensitive Detection of Cardiac Troponin I

Abstract: Porphyrins easily aggregate due to unfavorable π-π accumulation, causing luminescent quenching in the aqueous phase and subsequently reducing luminescent efficiency. It is a feasible way to immobilize porphyrin molecules through metal–organic framework materials (MOFs). In this study, 5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin (TCPP) was introduced into the metal–organic skeleton (PCN-224) as a ligand. The result showed that the electrochemiluminescence (ECL) and photoluminescence (PL) efficiency of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…14 Lu et al reported a sandwich-type ECL immunosensor based on Zr 6 -5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin framework (PCN-224) for the determination of cardiac troponin I. 15 Li's team proposed a new zirconium metal−organic framework (Zr-DPA@TCPP) as a single luminophore, which showed synchronous anodic and cathodic ECL signals. 16 Chen et al exploited a cage-like porous complex as the microreactor to attenuate the aggregation-caused quenching effect of mesotetra(4-carboxyphenyl) porphine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Lu et al reported a sandwich-type ECL immunosensor based on Zr 6 -5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin framework (PCN-224) for the determination of cardiac troponin I. 15 Li's team proposed a new zirconium metal−organic framework (Zr-DPA@TCPP) as a single luminophore, which showed synchronous anodic and cathodic ECL signals. 16 Chen et al exploited a cage-like porous complex as the microreactor to attenuate the aggregation-caused quenching effect of mesotetra(4-carboxyphenyl) porphine.…”
Section: Introductionmentioning
confidence: 99%
“…Since Bard’s group first reported the ECL properties of porphyrins, the development and investigation of porphyrins as ECL emitters are now in the ascendant . Lu et al reported a sandwich-type ECL immunosensor based on Zr 6 -5,10,15,20-tetrakis (4-carboxyphenyl) porphyrin framework (PCN-224) for the determination of cardiac troponin I . Li’s team proposed a new zirconium metal–organic framework (Zr-DPA@TCPP) as a single luminophore, which showed synchronous anodic and cathodic ECL signals .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic framework (MOF) is a kind of crystalline material with a periodic framework structure consisting of organic ligands as bridges and central metal ions or clusters as nodes. , With a designable structure and function of the MOF material, the prepared MOF can be obtained with desired and excellent performance. , Thus, MOF as a ECL luminophore has broad application space and has enormous potential for fabricating the coreactant-free ratiometric biosensor. It is gratifying that some MOF luminophores have been developed, which achieved coreactant-free or dual-emission ECL.…”
Section: Introductionmentioning
confidence: 99%